2022
DOI: 10.3390/mi13081265
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticle Encapsulation of Antibacterial Essential Oils

Abstract: Chitosan is the most suitable encapsulation polymer because of its natural abundance, biodegradability, and surface functional groups in the form of free NH2 groups. The presence of NH2 groups allows for the facile grafting of functionalized molecules onto the chitosan surface, resulting in multifunctional materialistic applications. Quaternization of chitosan’s free amino is one of the typical chemical modifications commonly achieved under acidic conditions. This quaternization improves its ionic character, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 168 publications
2
33
0
Order By: Relevance
“…These results are similar to those in the former investigation, except for results of microencapsulation efficiency of lemongrass oil using spray drying where %EE was 84.75% [35]. However, %EE of lemongrass oil encapsulated in CS nanoparticles was 44.82% AE2.80% as investigated by Negi and Kesari [36].…”
Section: Characterization Of Citralsupporting
confidence: 90%
“…These results are similar to those in the former investigation, except for results of microencapsulation efficiency of lemongrass oil using spray drying where %EE was 84.75% [35]. However, %EE of lemongrass oil encapsulated in CS nanoparticles was 44.82% AE2.80% as investigated by Negi and Kesari [36].…”
Section: Characterization Of Citralsupporting
confidence: 90%
“…Specifically, it has been reported that the electrostatic interaction between curcumin and chitosan nanoparticles has a strong correlation with the number of intermolecular hydrogen bonds [ 48 ]. As it is well known, -NH 2 groups onto this polysaccharide allow its chemical derivatization and grafting to improve its physicochemical properties [ 49 ], where one of the objectives is to enhance the water solubility of this macromolecule, increasing the permeability of hydrophobic nutraceuticals, rising the potential of loaded particles as carriers for oral delivery [ 50 ]. Regarding mucins, which are glycoproteins that are the major constituents of the intestinal mucus layer, their interaction with the chitosan backbone depends on the properties of both (mucins and the polymer) and can occur via electrostatic interactions, hydrogen bonding and hydrophobic interactions [ 24 ]; the amino groups of chitosan can bind to the sialic acid of mucins resulting in a better mucoadhesion [ 25 ], as well as the change in the surface’s charge (from negative to positive) of chitosan could trigger an increase in the adhesion of loaded particles on the intestinal mucosa [ 25 , 51 ].…”
Section: Biomedical Application Of Chitosan: Encapsulation Of Active ...mentioning
confidence: 99%
“…It is also possible for nanomaterials to supply medicines to bacterial cells that are implanted within an EPS matrix. Carvacrol oil, oregano essential oil, and thyme essential oil are three examples of potent antimicrobial oils that are unable to or poorly penetrate biofilms . It was reported that multiple drug-resistant biofilms were successfully eradicated utilizing carvacrol in oil-in-water cross-linked polymeric nanocomposites with limited damage to mammalian cells for Gram-positive and Gram-negative bacteria infections .…”
Section: Strategies Used To Treat Biofilmsmentioning
confidence: 99%
“…ROS are oxidative metabolic byproducts that occur within cells. These byproducts affect cells’ differentiation, signaling, survival, and death . The buildup of toxic levels of reactive oxygen species (ROS) causes oxidative stress (Figure ).…”
Section: Antimicrobial Mechanism Of Nanoparticlesmentioning
confidence: 99%